Sudan : Staff Report for the 2005 Article IV Consultation, Final Review of the 2004 Staff-Monitored Program, and the 2005 Staff-Monitored Program; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Sudan. (IMF Staff Country Reports; Country Report, 2005)
This paper examines Sudan's 2005 Article IV Consultation and the Final Review of the 2004 and 2005 Staff-Monitored Program (SMP). Between 2001 and 2004, the economy of Sudan grew at an average rate of 6.4 percent per year, and the non-oil sector expanded at an annual rate of 5.3 percent. The program for 2005 is based on prudent financial policies. The program will need to be adjusted by midyear to reflect additional financing arising from higher oil prices and aid and previously unfunded expenditures on social and infrastructure projects.